Outcome of pregnancies referred to a general practitioner maternity unit in a district hospital. Issue 6707 (28th October 1989) - Prentice, A.; Walton, S. M.
Abstract : OBJECTIVE–To audit the outcome of pregnancies booked for confinement in a general practitioner maternity unit in a district general hospital. DESIGN–Retrospective review of case records. SETTING–General practitioner maternity unit in a district general hospital. PATIENTS–685 Women referred to a general practitioner unit in 1987. RESULTS–315 Nulliparous women and 330 multiparous women were booked for confinement; 202 women transferred to consultant care before delivery and a further 104 during labour or after delivery. Recognised risk factors, other than nulliparity, rarely predicted the need for transfer. Confinement in the general practitioner unit was associated with low intervention and good fetal outcomes. CONCLUSIONS–The general practitioner maternity unit provides a safe alternative for confinement in low risk pregnancies. High rates of transfer deny this facility to many women who desire confinement in a low technology environment.